Immature stages of Calycopis bellera (Hewitson) and C. janeirica (Felder) (Lepidoptera, Lycaenidae, Theclinae, Eumaeini): Taxonomic significance and new evidence for detritivory - Duarte, Marcelo; Robbins, Robert K. (Zootaxa, 2009)
Details of egg, larval, and pupal morphology are described and illustrated for Calycopis bellera (Hewitson) and C. janeirica (Felder), with a special emphasis on larval chaetotaxy. Wild-caught Calycopis females laid eggs on dead leaves in the laboratory, and the caterpillars successfully completed development on an artificial agar diet to which no leaves were added. Males and females of the sexually dimorphic C. bellera had been previously placed in different genera or different species groups. Calycopis janeirica had been chronically misidentified (and misspelled C. jeneirica). Males and females of this species appear to be correctly associated for the first time. Whereas C. bellera has five larval instars—as reported previously for C. caulonia—C. janeirica has four. Morphological characters of the immatures of C. bellera and C. janeirica are summarized in a table and compared with those of other reared Calycopis species.